The ARID1A pathway in ovarian clear cell and endometrioid carcinoma, contiguous endometriosis, and benign endometriosis. Issue 1 (July 2015) - Chene, Gautier; Ouellet, Veronique; Rahimi, Kurosh; Barres, Veronique; Provencher, Diane; Mes-Masson, Anne Marie
Abstract: Objective: To assess ARID1A -encoded protein (BAF250a) and phosphorylated AKT (pAKT) expression, apoptosis, and the DNA damage response pathway in endometrioid and clear cell ovarian cancers (endometriosis-associated ovarian cancers [EAOCs]), and benign endometriotic ovarian cysts. Methods: In a retrospective study, tissue samples were reviewed from patients who had undergone surgery for EAOC or endometriotic ovarian cysts at a center in Montreal, QC, Canada, between 2000 and 2012. A tissue microarray including cases of endometrioid carcinoma, clear cell carcinoma, contiguous endometriosis (i.e. apparently benign endometriosis near the EAOC), and benign endometriotic ovarian cysts, was analyzed for the expression of various proteins. Results: Loss of BAF250a expression was seen in 13 (22%) of 59 endometrioid cancers, 17 (47%) of 36 clear cell cases, 8 (44%) of 18 contiguous endometriosis cases, and 3 (8%) of 66 benign endometriotic ovarian cysts. In tissues showing loss of BAF250a, expression of pAKT, γH2AX, BIM, and BAX was higher in EAOC and contiguous endometriosis than in benign endometriosis ( P  < 0.05), whereas expression of pATM, pCHK2, and Bcl2 was low. All proteins except for Bcl2 showed low expression in benign endometriosis. Conclusion: Loss of ARID1A -encoded protein seems to be an early event in EOAC, along with pAKT activation, alteration of γH2AX, and concomitant activation of the apoptosis pathway.